2020
DOI: 10.17843/rpmesp.2020.373.6126
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome inflamatorio multisistémico asociado a COVID-19 en niños: serie de casos en un hospital pediátrico de Perú

Abstract: La pandemia de COVID-19 ha traído una nueva afección grave e inusual denominada Síndrome Inflamatorio Multisistémico en niños, de la cual aún hay mucho por conocer. Presentamos una serie de 8 casos atendidos en el Instituto Nacional de Salud del Niño, Lima Perú. La edad media fue 5,1 años. La presentación clínica incluyó fiebre, problemas gastrointestinales agudos, afectación ocular y mucocutánea. Cuatro cumplieron criterios para Enfermedad de Kawasaki clásica. Todos tuvieron serología positiva para SARS-CoV-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 11 publications
(102 reference statements)
2
6
0
8
Order By: Relevance
“…An increase of CPR and Dimer-D was fundamentally observed in this study. In accordance to findings in literature, a variety of laboratory alterations have been described in COVID-19, especially in inflammatory serum markers (6, 15, 23, 24) a study found high levels of CPR, procalcitonin, interleukin-6, ferritin and Dimer-D in relation to severity (23). Our findings could have been explained by the elevated proportion of patients with mild symptoms, moderate and because only initial tests were included in the analysis.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…An increase of CPR and Dimer-D was fundamentally observed in this study. In accordance to findings in literature, a variety of laboratory alterations have been described in COVID-19, especially in inflammatory serum markers (6, 15, 23, 24) a study found high levels of CPR, procalcitonin, interleukin-6, ferritin and Dimer-D in relation to severity (23). Our findings could have been explained by the elevated proportion of patients with mild symptoms, moderate and because only initial tests were included in the analysis.…”
Section: Discussionsupporting
confidence: 86%
“…In relation to MIS-C cases, 6 patients with MIS-C diagnostic were found and 2 required PICU admission similar to what was described in another Peruvian report (⅛) (24). Meanwhile, in another study MIS-C cases represented 5 time more probabilities of PICU admission, however, no MIS-C patient died (6).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It is interesting that pediatric ADEM cases reported to date represent 30% of ADEM associated with COVID-19 (Table 2), which suggests that although it is a rare event, physicians should assess carefully neurological symptoms as part of the post-COVID-19 follow-up in children. Another point to highlight is that ADEM-like cases have been described in the context of an entity called MIS-C ( Abdel-Mannan et al, 2020 ; Lindan et al, 2020 ; Mehra et al, 2020 ) reported to appear between 10 and 54 days after COVID-19 infection ( Cheung et al, 2020 ; Coll-Vela et al, 2020 ; Toubiana et al, 2020 ; Verdoni et al, 2020 ; Whittaker et al, 2020 ). However, these MIS-C cases that have presented ADEM-like lesions do not have a confirmatory test for COVID-19 (they only have positive IgG serology) and were not considered in this review.…”
Section: Discussionmentioning
confidence: 99%
“…Un gran porcentaje ha requerido manejo por una unidad de cuidados intensivos (UCI) (2) . En el Perú existen varios centros que atienden el SIM-P, pero hasta el momento sólo se ha reportado una serie de casos de ocho pacientes (4) . Por lo tanto, con el objetivo de describir el perfil clínico-epidemiológico, mejorar su manejo, y disminuir su morbimortalidad; reportamos los resultados preliminares de 37 casos de SIM-P del Hospital Nacional Edgardo Rebagliati Martins (HNERM), en Lima, Perú, desde abril a agosto del 2020.…”
unclassified